The Lingering Killer: Agent Orange - Ungerfeld, Sharon (2014)
This paper explores the utilization of the chemical herbicide, Agent Orange, as it was sprayed over Vietnam during the Vietnam War in 1961 to 1971. The United States government, military, and corporations acted irresponsibly by creating the chemical and spraying it as a war tactic. The outcome of the spraying includes detrimental socioeconomic impacts, environmental degradation, and health problems. The socioeconomic impact is explained with statistics and an explanation of loss of job and education capabilities. With data on the destroyed trees and vegetation, this paper demonstrates the degree to which the environment faced harm. The health effects of Agent Orange are detailed by listing the diseases associated with the chemical. The struggle for justice, reparations, and policies remedying the harmful effects of Agent Orange are explored. Conclusions are made about the failing human rights record of the United States